2008
DOI: 10.1351/pac200880030519
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of annulenic subunits of graphyne and graphdiyne nanoarchitectures

Abstract: This report describes the synthetic strategies toward and optoelectronic properties of substructures of the non-natural, planar carbon networks graphyne and graphdiyne, which are based on the dehydrobenzo[12]annulene and dehydrobenzo[18]annulene framework, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
285
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(294 citation statements)
references
References 120 publications
(48 reference statements)
4
285
0
Order By: Relevance
“…1 can be assumed to be chemically stable. Indeed, finite building blocks and cutouts have already been synthesized [22,23,[25][26][27][28][29][30], and first steps towards the preparation of extended graphynes and graphdiynes have been proposed and developed [22,24,26,27]. Future synthesis of graphyne materials might involve the use of surfaces as support and templates in approaches related to the recently reported synthesis of graphene on metal surfaces by chemical vapor deposition of organic precursor molecules [12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…1 can be assumed to be chemically stable. Indeed, finite building blocks and cutouts have already been synthesized [22,23,[25][26][27][28][29][30], and first steps towards the preparation of extended graphynes and graphdiynes have been proposed and developed [22,24,26,27]. Future synthesis of graphyne materials might involve the use of surfaces as support and templates in approaches related to the recently reported synthesis of graphene on metal surfaces by chemical vapor deposition of organic precursor molecules [12][13][14][15][16][17][18].…”
mentioning
confidence: 99%
“…[25][26][27][28][29] Subsequent studies suggest that these materials have attractive electronic properties. [29][30][31][32][33][34][35] L. D. Pan et al reported that graphyne nanoribbons are semiconductors with band gaps similar to silicon.…”
mentioning
confidence: 99%
“…1). Indeed, assembled subunits of several graphyne structures [26][27][28] and another similar graphene allotrope including triple-bonded carbon linkages, so-called graphdiyne films and nanoribbons have already been synthesized. 29,30 Theoretical calculations have shown that these lowdimensional structures have unique mechanical, 24,[31][32][33] thermal, 34,35 optical, 36 and particularly electrical [37][38][39][40][41][42] properties as peculiar as those of graphene.…”
mentioning
confidence: 99%